Network Science and Cybersecurity - Pino, Robinson E.; Pino, Robinson E. (Advances in Information Security,, 2014)
Network Science and Cybersecurity introduces new research and development efforts for cybersecurity solutions and applications taking place within various U.S. Government Departments of  Defense, industry and academic laboratories. This book examines new algorithms and tools, technology platforms and reconfigurable technologies for cybersecurity systems. Anomaly-based intrusion detection systems (IDS) are explored as a key component of any general network intrusion detection service, complementing signature-based IDS components by attempting to identify novel attacks.  These attacks  may not yet be known or have well-developed signatures.  Methods are also suggested to simplify the construction of metrics in such a manner that they retain their ability to effectively cluster data, while simultaneously easing human interpretation of outliers. This is a professional book for practitioners or government employees working in cybersecurity, and can also be used as a reference.  Advanced-level students in computer science or electrical engineering studying security will also find this book useful . .